Introduction - Jon R. Conte (Journal of Forensic Social Work, 2013)
There is no question that the scope and complexity of forensic practice has expanded over the past two decades, as has the scientific evidence for vari-ous issues which come before Courts throughout much of the world. The rule of law is a hallmark of democratic societies. The pursuit of justice is not just the concern for legal professionals, but a wide range of professionals whose clients’ lives are touched by law or law breakers. The application of the best available evidence applied through a professional practice which is unbiased, reliable, and seeks the truth is the hallmark of a forensic expert. It is meaningless to try to balance one injustice against another injus-tice. The mentally ill adult, battered woman, as well as the child who becomes the victim of injustice, all suffer an outrage in a free society. Injustice whether because of biased testimony or ill-informed knowledge makes the forensic “expert” no expert at all. As children are among the most unheard, oppressed, and easy victims of those who break the law, forensic practice with children makes the duties of the expert even more critical than in areas where the subject of forensic practice is better able to speak for and advocate for her/himself or where scientific findings are robust and clear. In no area of the law or forensic practice is the pursuit of new knowledge more critical than it is practice with children. The manuscripts in this Special Issue rise out of the need for new knowledge to inform forensic practice with children. We are fortunate to have articles from among the leading researchers and experts on areas of knowledge that directly impact forensic practice with children. Each article expands our knowledge of forensic practice with and for children.